2022
DOI: 10.3390/ijms23084186
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Behavior of Right Atrial Myocardium of Healthy Rats and Rats with the Experimental Model of Pulmonary Hypertension

Abstract: There is a lack of data about the contractile behavior of the right atrial myocardium in chronic pulmonary heart disease. We thoroughly characterized the contractility and Ca transient of isolated right atrial strips of healthy rats (CONT) and rats with the experimental model of monocrotaline-induced pulmonary hypertension (MCT) in steady state at different preloads (isometric force-length), during slow force response to stretch (SFR), and during post-rest potentiation after a period of absence of electrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0
19

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(36 citation statements)
references
References 41 publications
5
12
0
19
Order By: Relevance
“…To better describe RA function and evaluate the susceptibility of the tissue to develop arrhythmias, we studied RA mechanical function from CTRL and MCT animals. A previous study reported that RA strips, from CTRL and MCT rats 24 to 28 days after the beginning of the experiments, once electrical stimulated at 2 Hz at 30°C did not present any changes in the mechanical properties of the tissue 7 . Interestingly, in a previous report using RA under sinus node beating frequency 14 days after MCT administration in rats, we found a faster contraction and relaxation time in the RA of MCT rats compared to the CTRL 20 .…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…To better describe RA function and evaluate the susceptibility of the tissue to develop arrhythmias, we studied RA mechanical function from CTRL and MCT animals. A previous study reported that RA strips, from CTRL and MCT rats 24 to 28 days after the beginning of the experiments, once electrical stimulated at 2 Hz at 30°C did not present any changes in the mechanical properties of the tissue 7 . Interestingly, in a previous report using RA under sinus node beating frequency 14 days after MCT administration in rats, we found a faster contraction and relaxation time in the RA of MCT rats compared to the CTRL 20 .…”
Section: Discussionsupporting
confidence: 42%
“…A previous study reported that RA strips, from CTRL and MCT rats 24 to 28 days after the beginning of the experiments, once electrical stimulated at 2 Hz at 30 C did not present any changes in the mechanical properties of the tissue. 7 Interestingly, in a previous report using RA under sinus node beating frequency 14 days after MCT administration in rats, we found a faster contraction and relaxation time in the RA of MCT rats compared to the CTRL. 20 This is in line with the recent observation that spontaneous activity of sinoatrial-node preparations from rabbits treated with MCT show faster beat rates.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Some groups have reported that RA mechanical function is not compromised in MCT rats. In one study, the authors treated rats with MCT and between 24 and 28 days later evaluated RA strips under electrical stimulation at 2 Hz at 30°C 31 and reported no significant change in the mechanical properties of the tissue. However, in our study, we found that RA function was compromised in the MCT rats.…”
Section: Discussionmentioning
confidence: 99%